Saudia Arabia Faces the 1980s: Saudi Security Problems and American Interests - Bloomfield Jr., Lincoln P. (Tufts Archival Research Center, 2005)
Volume 5, Issue 2. Summer The recent controversy over the sale of advanced weapons systems to Saudi Arabia and the decision of the Reagan Administration, albeit reservations, to support such a sale, has brought the desert kingdom back into sharp focus for American strategy and policy planners. While its medieval political and social structure grapples with modernization and the pressures of a vast accumulation of petrodollars, Saudi Arabia remains a critical element in American policy in the Middle East. In light of the ruthless invasion of Afghanistan by the Soviet Union and the Muslim fratricide of the Iran-Iraq war, the stability and longevity of the Saud family and the kingdom they rule have become more important - and problematic. In the following essay, Lincoln Bloomfield, Jr., presents a penetrating analysis of some of the internal and external pressures on Saudi Arabia, its princes, and the Washington-Moscow-Riyadh axes of tension and influence.